Bevel Structure Based XPS Analysis as a Non‐Destructive Chemical Probe for Complex Interfacial Structures of Organic Semiconductors. Issue 5 (10th April 2021) - Yun, Dong‐Jin; Lee, Seunghyup; Kim, Seong Heon; Jung, Changhoon; Kim, Yong Su; Chung, Jae Gwan; Heo, Sung; Kwon, Young‐Nam; Lee, Eunha; Kim, Ji‐Seon; Ko, Dong‐Su; Kim, Se Yun
Abstract: The bevel structure of organic multilayers produced by finely controlled Ar gas cluster ion beam sputtering preserves both the molecular distribution and chemical states. Nevertheless, there is still an important question of whether this method can be applicable to organic multilayer structures composed of complex or ambiguous interfaces used in real organic optoelectronic devices. Herein, various bevel structures are fabricated from different types of organic semiconductors using a solution‐based deposition technique: complicatedly intermixed electron‐donor and electron‐acceptor bulk heterojunction structure, thin film structure with an internal donor‐acceptor concentration gradient, and multi‐layered structure with more than three layers. For these organic material combinations listed above, the bevel structure is fabricated with finely tuned Ar gas cluster ion beam sputtering. The location‐dependent X‐ray photoelectron spectroscopy (XPS) results obtained for each bevel structure exactly correspond to the XPS depth profiles. This result demonstrates that the bevel structure analysis is a powerful method to distinguish subtle differences in chemical component distributions and chemical states of organic semiconductors even with complex or ambiguous interfaces. Ultimately, due to its reliability as verified by this study, the proposed bevel structure analysis is expected to greatly expand other analytical techniques with a limited spatial or depth resolution. Abstract : Bevel structures of various multilayered organic semiconductors are fabricated by finely controlled Ar gas cluster ion beam sputtering. The location‐dependent X‐ray photoelectron spectroscopy (XPS) results of the bevel structures exactly correspond to the XPS depth profiles. The bevel structure analysis could distinguish subtle differences in chemical component distributions and chemical states of complex multilayered organic semiconductors.